2021
DOI: 10.1007/s00405-021-07203-8
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies of SARS-CoV-2 testing results among patients with total laryngectomy

Abstract: Purpose Prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is obtained with nasopharyngeal swabs. By the way, there is no consensus regarding sampling in totally laryngectomized subjects (who thus breathe directly by the tracheostomy and, theoretically, may be infected in the trachea). The aim of this study is to evaluate possible differences between swab results in the trachea and in the nasopharynx of this category of patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The discordance of upper and lower respiratory samples has been previously documented. Specifically, a recent study evaluated differences between swab results in the trachea and in the nasopharynx in 25 totally laryngectomized subjects, showing that results were overall divergent and no statistically significant correlations emerged between results of the tests performed in the two sites, suggesting that both tracheal and nasopharyngeal swabs are recommended in these kinds of patients, to obtain a reliable test and to avoid false negatives ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The discordance of upper and lower respiratory samples has been previously documented. Specifically, a recent study evaluated differences between swab results in the trachea and in the nasopharynx in 25 totally laryngectomized subjects, showing that results were overall divergent and no statistically significant correlations emerged between results of the tests performed in the two sites, suggesting that both tracheal and nasopharyngeal swabs are recommended in these kinds of patients, to obtain a reliable test and to avoid false negatives ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] The relationship between COVID-19 and total laryngectomy patients was mentioned in two studies. [24][25][26] One of these studies reported that COVID-19 may show a more severe clinical course. [24] In our study, we found that COVID-19 was less frequent in total laryngectomy patients compared to the control (p=0.001).…”
Section: Discussionmentioning
confidence: 99%